Historical Compensation: The Eye of the Beholders - Nepali, Reemaya; Bhatta, Tara Datta (Tribhuvan University Journal, 2016)
This article presents the subalterns’ perspectives on government’s scholarship program in Badbhanjyang-1, Basundol, and Kathmandu. The information was analyzed and discussed using Spivak’s (1988) subaltern theory to understand Dalit as special ability group and Bourdieu’s cultural capital (1986) to know their different cultural assets at least in the field of education. This study showed that scholarship program was useful to educate and encourage the Dalit children to enroll in school. However, parents had to cover the additional expenses like exam fees, stationeries, and reference books. This additional financial burden to the parents had forced them to send their children for labor work rather than sending them to school. According to them, the scholarship program has not addressed the caste based social hierarchies rather it enforced them to feel themselves as inferior being ‘Dalit’ because it was given on the basis of the caste, as historical compensation to educate them.